Pendampingan Strategi Pemasaran UMKM Two Sides Apparel Salatiga dengan Memanfaatkan Digital Marketing - Pamungkas, Yohanes Tegar; Prakosa, Bernardus Novan Jaya Sukma; Mawardani, Lidya Krisma; Ramadhani, Nova Varazettira; Sugiarto, Agus (Universitas Nusantara PGRI Kediri, 2025)
Two Sides Apparel MSMEs experience obstacles in digital marketing, due to a lack of knowledge about the concept of digital marketing. The community service team intends to maximize the digital marketing potential of these MSMEs through mentoring and training activities. This activity was carried out for four months, with training and mentoring methods. These activities include the basics of digital marketing such as making product catalogs, social media content, and content calendars. Some of the tools used for this community service activity are Google Sites to create a website, Canva to create catalog designs and content, Capcut to create video content and also Whatsapp Business to maximize customer communication with Two Sides Apparel. The results of this activity show that business owners' understanding and social media activities have increased. Thus, these MSMEs have been able to utilize these digital marketing tools optimally.